Antecedents of human-robot collaboration: theoretical extension of the technology acceptance model - Parvez, M. Omar; Arasli, Huseyin; Ozturen, Ali; Lodhi, Rab Nawaz; Ongsakul, Viput (Emerald Group Publishing Ltd, 2022)
Purpose This study aims to extend the technology acceptance model (TAM) to examine whether the introduction of robots influences employees' behavioral intentions to use robots and awareness of robots to promote human-robot collaboration (HRC). Besides, the role of strategic human resource management (HRM) involvement as a moderator in the perception of robots as a team member was investigated. Design/methodology/approach Data were collected from 500 respondents via the Amazon Mechanical Turk platform. After data cleaning, 329 valid responses were analyzed. Partial least squares structural equation modeling was applied using Smart PLS Ver. 3.0 to test the study's measurement and proposed research model. Findings The study results show that robots' perceived usefulness and ease of use positively influence employees' behavioral intentions to use robots. In addition, the advantages and disadvantages of robots have a positive impact on robot awareness. Employees' behavioral intentions and awareness contribute positively to HRC. On the other hand, the moderating role of strategic human resources (HR's) involvement in the relationships was insignificant. Research limitations/implications This study provides an exclusively applied understanding of robot presence and embodiment relevant to real-world HRC. In the travel, tourism and hospitality (TTH) industry, employees' intention to use robots and robot awareness are significant factors. However, HRM involvement without the acceptance of robots could not enhance HRC. Originality/value Based on the literature review, to the best of the authors' knowledge, this study is one of the first on this topic and extends TAM with new antecedents related to robot use, robot awareness and HRC in the TTH industry. In addition, this model attempts to determine the factors that favor HRC in the industry. This study also assessed the moderating role of strategic HR's involvement in the behavioral intention of robot use, robot awareness and HRC.
Keywords: Hospitality; Service robots; Strategic HRM; Human-robots collaboration; Robot adoption; ??????; ?????; ?????; ????; ??